Integration of Religion and Education: A Conceptual Analysis of Islamic Values within the Framework of the Sociology of Education - Hamam Aqil Barid; Tutuk Ningsih (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This paper examines the integration of Islamic education and the sociology of education perspective as a response to the crisis of dehumanization in modern education. Modern education, which tends to emphasize cognitive and instrumental aspects, has neglected the spiritual and moral dimensions of humankind. Through the approaches of classical sociologists such as Émile Durkheim and Talcott Parsons, as well as the thoughts of Muslim scholars such as Hasan Langgulung, Syed Muhammad Naquib al-Attas, and Abdurrahman an-Nahlawi, this article demonstrates that Islamic education offers a holistic educational model. By making tawhid (Islamic unity) the foundation, morality the goal, and worship the integration of knowledge and practice, Islamic education can shape perfect human beings who are not only intellectually intelligent but also morally, spiritually, and socially sound. This conceptualization positions Islamic education as a humanistic, transformative, and relevant alternative solution in addressing global challenges.